Tinjauan Yuridis Penyelesaian Kredit Bermasalah Melalui Lelang Hak Tanggungan - Rena Anggi Permatasari; Binov Handitya (Universitas Ngudi Waluyo, 2023)
Non-performing Loan is a condition where the debtor cannot pay his debts to creditors on time. In this credit, of course, there are guarantees that must be given to creditors, one of which is the guarantee of a Mortgage. If there is a problem with credit and the debtor cannot fulfill his obligations, then this Mortgage guarantee can be up for auction. This research was conducted with the aim of finding out how the process of settling non-performing loans through auctions of mortgages is in accordance with predetermined rules. This research was conducted at the Semarang State Property and Auction Service Office using qualitative methods and a normative juridical approach, combining secondary and primary data materials. The secondary data the researcher took was from the library while the primary data the researcher took was from the results of the interviews that the researchers carried out at the Semarang State Property and Auction Services Office. From the results of the research that the researchers have done, the problem of loans made by debtors can be caused by several factors, namely internal factors, debtor factors, or external factors. If in the process of solving problem loans carried out by the bank, the debtor does not fulfill them, then it can be carried out through the Mortgage auction stage according to Minister of Finance Regulation Number 213 of 2020 and Law Number 4 of 1996. Abstrak Kredit bermasalah merupakan suatu keadaan dimana debitur tidak mampu membayar hutang yang dimilikinya kepada kreditur dengan tepat waktu. Dalam perkreditan ini tentu ada jaminan yang harus diberikan kepada kreditur, salah satunya adalah jaminan Hak Tanggungan. Jika terjadi kredit bermasalah dan debitur tidak mampu dalam memenuhi kewajibannya, maka jaminan Hak Tanggungan ini dapat sampai pada lelang. Penelitian ini dilakukan bertujuan untuk mengetahui bagaimana proses penyelesaian kredit bermasalah melalui lelang Hak Tanggungan sesuai dengan aturan yang telah ditetapkan. Penelitian ini dilaksanakan di Kantor Pelayanan Kekayaan Negara dan Lelang Semarang dengan menggunakan metode kualitatif dan pendekatan yuridis normatif yaitu menyatukan bahan-bahan dari data sekunder dan data primer. Data sekunder peneliti mengambil dari kepustakaan sedangkan data primer peneliti mengambil dari hasil wawancara yang telah peneliti laksanakan di Kantor Pelayanan Kekayaan Negara dan Lelang Semarang. Dari hasil penelitian yang telah peneliti lakukan, bahwa kredit bermasalah yang dilakukan oleh debitur dapat disebabkan oleh beberapa faktor yaitu faktor internal, faktor debitur, atau faktor eksternal. Jika dalam proses penyelesaian kredit bermasalah yang dilaksanakan oleh pihak bank tidak terpenuhi oleh debitur, maka dapat dilakukan melalui tahap lelang Hak Tanggungan sesuai dalam Peraturan Menteri Keuangan Nomor 213 Tahun 2020 dan Undang-Undang Nomor 4 Tahun 1996.